2005
DOI: 10.2175/106143005x41636
|View full text |Cite
|
Sign up to set email alerts
|

The Fate and Removal of Triclosan during Wastewater Treatment

Abstract: This work examines the variation in removal efficiency of triclosan in wastewater treatment works in the United Kingdom between November 2003 and April 2004. Concentrations of triclosan were measured at set points within three different types of wastewater treatment works: rotating biological contactors, trickling filters, and activated sludge. Overall removal of triclosan through these plants ranged from 58 to 96% (rotating biological contactors), 86 to 97% (trickling filter), and 95 to 98% (activated sludge)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 11 publications
3
53
0
3
Order By: Relevance
“…Anti-bacterial triclosan was detected both in in uent and e uent samples at concentration 0.166 g/L and 0.093 g/L, respectively and these results are comparable to those reported by Weigel and Thomas [27,29]. According to the literature data, conventional treatment plants remove pharmaceuticals compounds mainly during biological treatment with activated sludge [18,22,28]. Here, biodegradation or sorption to sludge is the probable mechanism of elimination [31].…”
Section: Resultssupporting
confidence: 72%
“…Anti-bacterial triclosan was detected both in in uent and e uent samples at concentration 0.166 g/L and 0.093 g/L, respectively and these results are comparable to those reported by Weigel and Thomas [27,29]. According to the literature data, conventional treatment plants remove pharmaceuticals compounds mainly during biological treatment with activated sludge [18,22,28]. Here, biodegradation or sorption to sludge is the probable mechanism of elimination [31].…”
Section: Resultssupporting
confidence: 72%
“…They raised concerns about a sorbed drug desorbing if environmental conditions change and sorption had been the compound's main removal mechanism. A change in environmental conditions did affect removal processes in a study by Thompson et al (2005) in which they observed that biodegradation was responsible for the majority of triclosan removal in WWTP processes when there were high dissolved oxygen levels. Yet in processes with lower oxygen levels, sorption became the dominant removal mechanism.…”
Section: Studies With Multiple Removal Mechanismsmentioning
confidence: 99%
“…However, several studies have indicated that estrogens, triclosan, caffeine, ibuprofen, and ciprofloxacin can be reduced or eliminated in biological wastewater treatment systems using the activated sludge (aeration basin) process, where sorption to particles and biotransformation are potential mechanisms of PPCP removal (Sedlak and Pinkston 2001;Giger et al 2003;Andersen et al 2005;Bester 2005; Thomas and Foster 2005;Thompson et al 2005;Nakada et al 2006;Kim et al 2008). It is also likely that some of PPCPs in this study were removed from wastewater via chlorination.…”
Section: Ppcps In Wastewatermentioning
confidence: 99%